Analysis of Voice in Yakshagana Singers - Usha Devadas; Rajashekar B; Venkataraja Aithal U. (Journal of All India Institute of Speech and Hearing)
Yakshagana (street play) is a performing art of Karnataka in which different channels of communication like dance, music, costume are utilized. Yakshagana songs are sung by a member of the troupe known as Bhagavata. Using a standard comparison study design, the parameters viz. fundamental frequency[F0], speaking fundamental frequency[SFF], jitter percent[JITT], shimmer dB[SH dB], noise to harmonic ratio[NHR]), maximum phonation duration(MPD) and S/Z ratio of Bhagavata’s voice were compared with age matched nonsingers. Results of the study revealed, significantly higher fundamental frequency, speaking fundamental frequency and reduced MPD in Bhagavatas as compared to their non-singing counterparts. Laryngeal evaluation (rigid telescopy) in Bhagavatas revealed signs of vocal abuse.